Answer:
x = -1 and y = -1
Step-by-step explanation:
Solve 3x+3y=−6;−x+y=0
Steps:
I will solve your system by substitution.
−x+y=0;3x+3y=−6
Step: Solve−x+y=0for y:
−x+y+x=0+x(Add x to both sides)
y=x
Step: Substitutexforyin3x+3y=−6:
3x+3y=−6
3x+3x=−6
6x=−6(Simplify both sides of the equation)
6x
6
=
−6
6
(Divide both sides by 6)
x=−1
Step: Substitute−1forxiny=x:
y=x
y=−1
Answer:
x=−1 and y=−1
if you isolate y in the bottom equation youll see that x=y so if you plug in y for x in the top equation youll get 6y=-6 then divide both sides by 6 to get y=-1 and since y=x x=-1
so it would be the last option where x and y both equal -1
Answer:
Step-by-step explanation:
When you have an inequality like this, you can treat it like an equation except for one part. If you ever divide or multiply it by a negative number or variable you have to flip the inequality. if it is equal to as well you keep that though. for instance
-5x ≤ 10
x ≥ -2
Anyway, in your case you have two inequalities, so you have to solve both and see what makes both true.
We'll start with 12x - 39 ≤ 9
12x - 39 ≤ 9 First add 39 to both sides
12x ≤ 48 Now divide both sides by 12, positive so no flipping
x ≤ 4
Next is:
-4x + 3 < -6 First subtract 3 from both sides
-4x < -9 Now divide both sides by -4, which means the sign flips
x > 9/4
Now, without even looking at the answers, what number or numbers are less than or equal to 4 and greater than 9/4? Well we pretty much described it there. All numbers starting from, though not including 9/4, which is 2.25, all the way up to, and including 4. B shows exactly that.
To solve the inequalities, the first is simplified to x > 4 and the second to x > 2.25 after applying proper arithmetic operations and considering the signs during division.
The student's question involves solving two inequalities, one of which is a linear inequality, and the other an inequality that requires adding or subtracting to isolate the variable. To solve the inequality 12x - 39 > 9, we add 39 to both sides to get 12x > 48, then divide both sides by 12 to find that x > 4. For the inequality -4x + 3 < -6, we subtract 3 from both sides to get -4x < -9, then divide by -4, remembering that dividing by a negative number reverses the inequality, resulting in x > 9/4 or x > 2.25.
#SPJ2
Please tell me how to do these types of questions as well as the answer